Data Privacy in Educational Contexts: Analyzing Perceptions, Practices and Challenges in Personal Data Protection - Extended Abstract CTDGSI 2025 - Barros, Yuri Correia de; Vilela, Jéssyka (Anais Estendidos do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2025: Anais Estendidos do XXI Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi_estendido.2025.246754, 2025)
This extended abstract presents a study on personal data privacy in educational contexts. Combining a survey and a systematic literature review, it analyzes perceptions, practices, and challenges in protecting student and teacher data. The findings reveal significant gaps in the privacy Brazilian law LGPD (Lei Geral de Proteção de Dados Pessoais) knowledge, inadequate training, and insufficient data security measures across institutions. In addition, discrepancies in data handling practices between professors and students are highlighted, emphasizing the need for clearer policies and improved transparency. Finally, the research contributes suggestions for future work aimed at enhancing regulatory compliance and fostering a culture of privacy in education.